Implementasi Kurikulum PAI Berbasis Kompetensi Dalam Meningkatkan Kualitas Pembelajaran Di SMK Kesehatan Nusantara Pamekasan - Agus Priyanto, Abd Rohman; Munawwarah, Ummu Diana; Sarkawi, Ach (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
This article discusses the implementation of competency-based Islamic Religious Education (PAI) curriculum in improving the quality of learning at Nusantara Health Vocational High School (SMK) Pamekasan. This study aims to examine and analyse the implementation of competency-based Islamic Education curriculum at SMK Kesehatan Nusantara. The research method used is a literature study with a qualitative approach. The results showed that the implementation of competency-based PAI curriculum has had a positive impact on the quality of learning at SMK Kesehatan Nusantara Pamekasan. The findings provide recommendations to continue to improve the development of competency-based PAI curriculum in order to improve the quality of education at the SMK.